The Effects of Financial Awards, Work Environment, and Market Considerations: Work on Career Selection as a Public Accountant for Accounting Students (Study of State and Private Universities in Gorontalo Province) - Imran Rosman Hambali; Ayu Rakhma Wuryandini; Sahmin Noholo (Journal of International Conference Proceedings (JICP), 2018)
This study aims to identify factors of financial reward, work environment and labor market considerations for career choice as a public accountant for accounting students. This study has been conducted at public and private university in Gorontalo Province. The sample collection of this study has been done by using purposive sampling with the criteria all students is in seventh semester and has made an audit course. The amount of sample is based on purposive sampling about 157 respondents used. Data processing is conducted by using Multiple Linear Regression Analysis. The results of this study inditify that financial rewards have a positive but not significant influence on career choice as a public accountant, while the work environment and labor market considerations are have a significant positive influence on career choice as a public accountant. Keywords: financial rewards; work environment; labor market considerations; career choice of Public Accountant.